2013
DOI: 10.12968/ajmw.2013.7.2.71
|View full text |Cite
|
Sign up to set email alerts
|

Women’s experiences of breastfeeding: A narrative review of qualitative studies

Abstract: Globally, breastfeeding remains the primary method of infant feeding. Despite the indisputable benefits of breastfeeding, studies have identified both positive and negative aspects of women’s experiences. This article aims to enhance our understanding of these breastfeeding experiences. Methods: Using a narrative review approach, 26 papers using different qualitative approaches were synthesized in order to consider the findings of real-life experiences of breastfeeding women. Selected qualitative studies descr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 29 publications
0
10
0
1
Order By: Relevance
“…2 Despite these figures, women are legally protected to breastfeed publicly (up to 26 weeks) by the Equality Act 2010 and any public service providers (eg, cafes, libraries, public transport, etc) have a legal obligation to protect breastfeeding women from discrimination. 3 Further qualitative research [4][5][6][7][8][9][10][11][12] highlights similar concerns to these reports, illustrating that a women's comfort to feed in public is related to the perceived social, cultural and public values around breastfeeding. It has been identified previously that such values may be derived from seeing very few women breastfeeding in public in the UK, 6 13 alongside a lack of breastfeeding support in TV, print and social media.…”
Section: Introductionmentioning
confidence: 78%
“…2 Despite these figures, women are legally protected to breastfeed publicly (up to 26 weeks) by the Equality Act 2010 and any public service providers (eg, cafes, libraries, public transport, etc) have a legal obligation to protect breastfeeding women from discrimination. 3 Further qualitative research [4][5][6][7][8][9][10][11][12] highlights similar concerns to these reports, illustrating that a women's comfort to feed in public is related to the perceived social, cultural and public values around breastfeeding. It has been identified previously that such values may be derived from seeing very few women breastfeeding in public in the UK, 6 13 alongside a lack of breastfeeding support in TV, print and social media.…”
Section: Introductionmentioning
confidence: 78%
“…'s (2013) review of qualitative studies exploring women's experiences of breastfeeding found that breastfeeding was experienced as a symbol of motherhood, connecting mother and baby. However, they also highlighted a dilemma of expectations vs. reality of breastfeeding and a need for n reassurance and support.…”
Section: Introductionmentioning
confidence: 99%
“…) and, as breastfeeding is a socio‐cultural construct (Afoakwah et al . ; Turner and Norwood ), it is important to understand whether and how women can negotiate mutual adjustments for breastfeeding in diverse cultural settings. The paucity of research on breastfeeding at work in the management and organizations literature is likely to be related to masculine ideas about workers and objection to leaky maternal bodies in the workplace (Gatrell ).…”
Section: Management Of the Return To Workmentioning
confidence: 99%